A taxonomic reassessment of Croton grandivelus, including recognition of a new species, C. insignis, and the redefinition of C. fulvus (Euphorbiaceae) - Sodre, Rodolfo Carneiro [UNESP]; Silva, Marcos Jose da (Magnolia Press, 2020)
Croton is one of the largest genera of Angiosperms, with a pantropical distribution and a high diversity in South America, where 500 of its species occur. Croton sect. Adenophylli, its largest section, is characterized mainly by the fruit columella with three terminal ascending and inflated appendices and is distributed across the Neotropics, with the Cerrado as one of its centers of diversity. One of the binomials in the section, Croton grandivelus, has been applied to a broadly circumscribed entity that is here treated as including three species, C. grandivelus sensu stricto, C. fulvus and C. insignis, the latter described as a new species. We present a taxonomic treatment for these three species with descriptions, photographs, an illustration for the new species, an identification key, distribution maps, and commentary on the taxonomy, geographical distribution, environmental preferences, conservation status, flowering and fruiting times, morphological relationships and notes about the leaf anatomy and micromorphology of foliar trichomes. As part of this process, we propose 23 new synonyms and 15 lectotypifications.
Keywords: Cerrado; Chaco; Croton sect; Adenophylli; Crotoneae; diversity; taxonomy; South America